PENGARUH INFLASI, BI RATE, KURS, CAR DAN FDR TERHADAP NON PERFORMING FINANCING BANK SYARIAH MANDIRI - Muhammad Fadlillah Fauzukhaq; Devita Sari; Suhenda Wiranata (Media Ekonomi, 2020)
This research aims to determine the influence Inflation, Bi rate, Kurs, Capital Adequency Ratio (CAR) and Financing to Deposite Rasio (FDR) variables against Non-Performing Financing (NPF) Mandiri Sharia banking. This research uses the Vector Auto Regression (VAR) and Vector Error Correction Model (VECM) methods. The variables used in the study consisted of inflation, BI Rate and exchange rate which classified into macroeconomic variables and Capital Adequency Ratio (CAR) and Financing to Deposite Ratio (FDR) belonging to the micro-economic variables. This research uses Bank Syariah Mandiri as a sample of research and data used in the form of financial statements published by the official website of Bank Syariah Mandiri. Root Unit testing, Optimum Lag, Model stability, and cointegration are used to view research data. Hypothesis testing uses Granger Causality to test simultaneously and VECM for partial testing and see long-term and short-term influences. The results showed that simultaneously inflation, Bi Rate, exchange rate, CAR and FDR have no influence on NPF Bank Mandiri Syariah. Then partially in the short term all variables also do not have a significant influence on NPF Bank Syariah Mandiri. But partially in long-term variable inflation, Bi Rate, exchange rate, CAR and FDR have a significant influence on NPF Bank Syariah Mandiri